A Pandemic (COVID-19) Which has Commutated the Political Future of Sublunary World - Swapnil Chaudhary (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
The country that has even braved the disastrous floods, serial bomb blasts and even the horrific November 2008 terror attack is unfortunately not ready and unable to tackle COVID 19. The tiny microbe that has swept almost world over infecting lakhs and lakhs of people with a high causality rate is considered more dangerous thus leading to a pandemic situation in the country. In anticipation of developing lean supply chains many sectors of our economy have started depending more and more supplies from China. In the present situation, valuable lessons have been leant by for companies in general and Indian companies in particular. Lean supply chain strategies which are capable of increasing short-term profitability of business could importunely make the supply chain highly vulnerable. Keywords:COVID-19, pandemic, supply chain operations, vulnerable, etc.